Public Relations Strategy in Socializing the KALIMASADA Program to Enhance Public Services: Study in Surabaya – Ketintang Sub-District - Priambodo, Lambang; Rosy, Brillian (Journal of Office Administration : Education and Practice, 2023)
The Kalimasada Program is a technology-based initiative initiated by the Civil Registration and Civil Registry Office (Dispendukcapil) of Surabaya City, designed to expedite Adminduk services for the residents of Surabaya. The process aims to enhance public services, thereby achieving the goals set by the program. This research aims to understand the public relations (PR) strategies employed by Ketintang Sub-District in promoting the Kalimasada Program to improve public services. The study is in the Ketintang Sub-District of Surabaya City. The research method used is qualitative with a descriptive qualitative approach through purposive sampling techniques for subject selection. The results of the research indicate that, overall, the public relations strategies employed by Ketintang Sub-District in promoting the Kalimasada Program have had a positive impact, as evidenced by an increase in the number of residents utilizing Adminduk services through the Kalimasada Program, although not yet to its full potential. The public relations strategies involve providing assistance to the RT (neighborhood association) leaders, utilizing social media platforms such as TikTok, Instagram, and WhatsApp, conducting face-to-face socialization with residents, and providing services at the already-socialized neighborhood community centers (balai RW). These PR strategies effectively promoted the Kalimasada Program and contributed to the improvement of public services. The success of these public relations strategies in promoting the Kalimasada Program is evident in residents' feedback, as they feel facilitated and experience faster Adminduk processing due to their awareness of the Kalimasada Program introduced by Ketintang Sub-District.